2001
DOI: 10.1007/bf02490339
|View full text |Cite
|
Sign up to set email alerts
|

Determination by high performance liquid chromatography of ornithine and lysine decaboxylases in sugar cane juices

Abstract: Accurate and very sensitive HPLC methods which allow the simuJtaneous determination of the diamines putrescine (PUT) and cadaverine (CAD), resulting from ornithine decarboxylase (ODC) and lysine decarboxylase (LDC) activities or naturally occurring in sugarcane juices, are presented. Diamines were detected as their dansyl derivatives by fluorescence emission. The corresponding limits of detection were 21 ng mL 1 for PUTand 5 ng mL 1 for CAD. HPLC methods were compared with routine spectrophotometric assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…In previous studies, it has been found that several enzymes related to polyamine biosynthesis occurred in sugarcane juice (Legaz et al 2001). Arginase was shown to be a glycoprotein synthesized by sugarcane plants in response to U. scitaminea infection (Millanes et al 2005).…”
Section: Changes In the Activity Of Arginase Odc And Ldc Enzymes Ofmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous studies, it has been found that several enzymes related to polyamine biosynthesis occurred in sugarcane juice (Legaz et al 2001). Arginase was shown to be a glycoprotein synthesized by sugarcane plants in response to U. scitaminea infection (Millanes et al 2005).…”
Section: Changes In the Activity Of Arginase Odc And Ldc Enzymes Ofmentioning
confidence: 98%
“…Assay of lysine decarboxylase LDC activity was assayed spectrophotometrically according to the method of Phan et al (1982) with the modifications described by Legaz et al (2001). The method is based upon the principle that CAD, a product of LDC activity, reacts with TNBS to give a product soluble in toluene.…”
Section: Extraction and Analysis Of Soluble And Conjugated Polyaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the most active fraction of sugarcane glycoproteins is related to polyamine biosynthesis, we assesses arginase activity of sugarcane juice contains several enzymes related to polyamine biosynthesis, mainly ornithine decarboxylase (Legaz et al 2001), using ornithine as a substrate produced by enzymatic hydrolysis of arginine. Moreover, glycosilated arginase produced by lichenized and pathogenic ascomycetes binds to the algal partner and alters the level of putrescine produced by the host cell (Molina et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Arginase activity was measured since sugarcane juice contains several enzymes related to polyamine biosynthesis, mainly ornithine decarboxylase (Legaz et al, 2001), which uses ornithine produced by enzymatic hydrolysis of arginine as a substrate. Moreover, glycosilated arginase produced by lichenized and pathogenic ascomycetes binds to the algal partner or changes the level of putrescine produced by the invaded cell (Molina et al, 1998).…”
Section: The Most Active Fraction Of Sugarcane Glycoproteins Is Relatmentioning
confidence: 99%